Basic problems of fibre-reinforced structural components when fibres resist bending - Farhat, Ali Farag (2013)
This thesis generates certain sets of analytical and approximate solutions to a new class of partial differential equations stemming from a version of asymmetricstress elasticity theory appropriate for the study and prediction of the behaviour of fibre-reinforced materials containing fibres that resist bending. These new solutions are of theoretical and practical interest in the static and dynamic analysis of thinwalled, linearly elastic fibre-reinforced structures influenced by couple-stress and unsymmetric stress due to fibre bending stiffness. The static and free vibration solutions are constructed considering bending resistance fibres in a small deformation of beams and plates. Numerical results for displacements, stresses, couple-stress and natural frequencies of vibration are provided to investigate the influence of the fibres resistance in bending on the deformed beams and plates.